What does a "theoretically-guided" intervention really look like? A guide for nursing and social science researchers - Morrison-Beedy, Dianne; Tóthová, Valérie; Červený, Martin (Kontakt, 2024)
Theoretical frameworks and models provide a roadmap for clinical practice and research by explaining and predicting the processes that influence intervention outcomes. They serve as the basis for understanding, conceptualizing, and designing nursing and social science intervention studies. Yet what is often not clearly understood is how theory actually guides intervention development and testing. What do we really mean when we describe an intervention as theoretically driven and how does a research scientist go about making this happen? The purpose of this article is to provide an exemplar of how theory guided the development of an evidence-based nursing intervention developed to reduce sexual risk behaviors (The Health Improvement Project for Teens). This approach can be used as a guide or framework applicable to other intervention programs in development. We also discuss the need in the Czech Republic for more rapid integration of broader theoretical approaches to guide intervention development and continued focus on the development and testing of nursing interventions. While still in its initial stages of development, nurse and social scientists in the Czech Republic can quickly build rigorous interventions by expanding the use of the broad array of useful theories that can guide intervention development.
Keywords: Psychometrics; Nursing; Unsafe Sex; psychosociální intervence; Adolescent; ošetřovatelství; hraní rolí; psychodrama; ošetřovatelství - vzorové postupy; teoretické modely; Motivation; Role Playing; mladiství; Practice Patterns, Nurses'; Models, Theoretical; lidé; motivace; psychometrie; Humans; rizikový sex; Sexual Behavior; sexuální chování; Psychosocial Intervention; Psychodrama